CLINICAL AND ANAMNESTIC ANALYSIS OF THE LABOR PROCESS OF MOTHERS OF BABIES BORN WITH PRIMARY ATELECTASIS. - Z.I. Ruziyeva (Scholar Express Journals, 2023)
In this study, the prevalence of risk factors and the pathogenetic mechanism of primary lung atelectasis of infants were studied in groups of premature and fullterm infants. A total of 98, including 52 premature, 46 full-term, clinical and anamnestic data and risk factors of primary pulmonary atelectasis were studied. The results showed that maternal diseases such as preeclampsia, infectious diseases, endocrine pathology and various extragenital diseases, as well as complications related to the birth process, are risk factors for the development of primary atelectasis in the lungs of newborns. Mother's age less than 20 or more than 35, preeclampsia, infectious diseases, complications of childbirth, child's head and brain injury and high level of birth defects were identified as risk factors. It was observed that primary atelectasis of the lungs occurs in premature babies in most cases, and the rate of development of diseases identified as a risk factor is also high.
Keywords: Infant; lung atelectasis; premature birth